Safe Manipulation of Humans in Robot-driven Physical Human-Robot Interaction. - Ruiz-Ruiz, Francisco Jesús (UMA Editorial, 2024)
Due to the emergence of collaborative robots, humans and robots have been working in close proximity, and in some tasks, even sharing a common goal. Under these circumstances, physical contact between human and robot has a high probability of occurrence, which has made the field of physical Human-Robot Interaction (pHRI) a hot research topic. Despite the impact that pHRI applications could have in society, the current state-of-the-art in this field is focused on collaboration, i.e., on how human and robot work together towards the completion of a given task minimizing the physical interaction between both. However, there still a lack of works about pHRI in which robots have a proactive role. This thesis tackles the challenge of studying and implementing robotdriven pHRI tasks. To this end, such a challenge is decomposed. First, a compliant underactuated gripper specifically designed for human limb grasping is introduced. The kinetostatic model of the gripper is computed, allowing for the estimation of the grasping and interaction forces. Secondly, a method to estimate the parameters of the kinematic model of a human upper-limb is presented. Such a method relies on the kinesthetic information of a robotic manipulator that moves the human limb, requiring only a simple ascendant motion. Finally, two controllers under the assist-as-needed paradigm are developed. The first one serve as a balance assistant with a collaborative manipulator. The second one assist the user in the following of a predetermined Cartesian path. In general, although some extra considerations should be taken into account the outcomes of this work lay the foundations for the implementation of a robot-driven pHRI task.
Keywords: Robótica; Interacción hombre-ordenador; Robots autónomos; Physical Human-Robot; Interaction; Assistive Robotics; Robotic Grippers; Parameter Estimation